Detecção do TAstV-2 (Turkey astrovirus type 2) em perus (Meleagris gallopavo) - Silva, Sérgio Eustáquio Lemos da (2008)
The reverse transcription polymerase chain reaction (RT-PCR) of turkey astrovirus (TAstV) capsid and polymerase gene was applied in the bursa of Fabricius (BF), thymus (TH), spleen (SP) and cloacal swabs (CS) from young poults with PEMS (Poult Enteritis Mortality Syndrome). The histological lesions were atrophy, lymphoid depletion, cellular infiltration and necrosis of BF, TH and SP, respectively. The RT-PCR reactions were positive in all of 100 CS, 7 out of 10 of BF, 10 out of 20 TH and SP, respectively, for the polymerase gene of TAstV-2. Five out of 10 TH and SP samples, considered as negative by RT-PCR, were positive when specific primers designed to the TAstV-2 capsid gene were applied. Finally, this is the first description of turkey astrovirus infection presenting PEMS in Latin America.